Efektivitas Dimensi Kualitas Service Terhadap Kepuasan Pengunjung Pada Objek Wisata Budaya Betawi-Setu Babakan - Indra Setiawan Purba; Septio Maulana; Prasetio Ariwibowo (Journal of Economics and Business Aseanomics (JEBA), 2018)
Â This research used Non Probability Sampling method with Convinience Sampling technique using 100 respondents in Jakarta. This research is to find out how big influence of service quality dimension to visitor satisfaction at Setu Cultural Attraction Object limited by using tangibles, reliability, responsiveness, empathy, and assurance aimed to test the effect of these variables on the satisfaction of visitors on the Object of Culture - Setu Babakan.Based on F-test, t-test, and multiple regression test indicate that service quality dimension consist of tangibles, reliability, responsiveness, empathy and assurance together or simultaneously affect the visitor's satisfaction significantly and the highest value that became evidence of success for the manager of Cultural Attraction Setu Babakan in providing high service to visitors.Based on the summary model ofÂ  R-Square test results, it can be seen that there is a strong correlation or correlation between service quality dimension with visitor satisfaction with value more than 50%.